2011
DOI: 10.1089/ham.2011.1020
|View full text |Cite
|
Sign up to set email alerts
|

No Correlation between Plasma Levels of Vascular Endothelial Growth Factor or its Soluble Receptor and Acute Mountain Sickness

Abstract: Increased plasma levels of vascular endothelial growth factor (VEGF) due to lower levels of its soluble receptor (sFlt-1) had been suggested to cause vasogenic brain edema and thereby to cause the symptoms of acute mountain sickness (AMS). We tested this hypothesis after active ascent to high altitude. Plasma was collected from 31 subjects at low altitude (100 m) before (LA1) and after (LA2) 4 weeks of aerobic exercise training in normobaric hypoxia or normoxia, and one night after ascent to high altitude (455… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
(32 reference statements)
0
15
0
Order By: Relevance
“…, Schommer et al . ). Alternatively, the soluble VEGF receptor (SFlt1) may bind circulating VEGF and reduce free plasma VEGF and therefore VEGF activity (Chen et al .…”
Section: Potential Drug Targets For Preventing Amsmentioning
confidence: 97%
See 1 more Smart Citation
“…, Schommer et al . ). Alternatively, the soluble VEGF receptor (SFlt1) may bind circulating VEGF and reduce free plasma VEGF and therefore VEGF activity (Chen et al .…”
Section: Potential Drug Targets For Preventing Amsmentioning
confidence: 97%
“…SNP rs3025039, but not SNP rs3025030, was also significantly associated with plasma VEGF levels. But there is no evidence of a direct association between plasma VEGF levels and AMS (Dorward et al 2007, Schommer et al 2011. Alternatively, the soluble VEGF receptor (SFlt1) may bind circulating VEGF and reduce free plasma VEGF and therefore VEGF activity (Chen et al 2000).…”
Section: Vegfmentioning
confidence: 99%
“…Evidence regarding VEGF from AMS studies remains controversial. Absolute values or changes in VEGF were not correlated with AMS scores [ 46 , 47 ]. On the other hand, Ding et al reported that among Chinese Han subjects ( n = 40), the AMS group had a higher VEGF plasma concentration than the control group at both sea level and HA [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strenuous physical work at high altitudes is accompanied by higher levels of VEGF and pulmonary artery pressure than exercise at sea level (36). Nonetheless, the absolute values of or changes in VEGF expression have not been shown to be correlated with AMS symptoms or scores (37). Hypoxia leads to increased hydrostatic pressure and blood‐brain barrier permeability in patients with acute ischemic stroke through VEGF (38).…”
Section: Discussionmentioning
confidence: 99%